Methicillin resistant staphylococcus aureus: awareness, knowledge and disposition to screening among healthcare workers in critical care units of a Nigerian hospital (2011)
BACKGROUND: Awareness level about methicillin resistant Staphylococcus aureus (MRSA) is high in the western world but the status in developing countries is not well defined. OBJECTIVE: To assess MRSA awareness level, knowledge and disposition to screening among critical healthcare givers (HCGs) in Nigeria. METHODS: A self-administered questionnaire was used to assess the level of awareness and knowledge of HCGs in critical care units of the University of Ilorin Teaching Hospital, Ilorin, Nigeria on MRSA and their willingness to submit to screening. RESULTS: Only 103 (52.0%) of the 198 participants were aware of MRSA but all were favourably disposed to screening for the organism. Awareness was through hospital rounds 65(63.1%) and journals/ textbooks 35(34.0%), and Many, 120 (60.6%) considered MRSA as a threat in the hospital, while only 27 (13.6%) thought otherwise and 51(25.8%) were indifferent. Most HCGs, 124 (87.9%) reported that there were no MRSA control measures in their respective duty post. The age, cadre of work, and number of years in the hospital’s critical care units correlated positively with awareness level. CONCLUSION: Methicillin resistant Staphylococcus aureus awareness level among the HCGs in our hospital is just a little above 50.0% with substantial proportion of them not realizing the medical implication of the organism. However, majority are well disposed to MRSA screening. Inadequate publicity is a major contributor to poor knowledge and awareness. There is need for educational intervention and sensitization programs on MRSA and other infection control techniques for HCGs in developing nations especially Nigeria.